2002
DOI: 10.1038/sj.leu.2402654
|View full text |Cite
|
Sign up to set email alerts
|

Karyotype instability between diagnosis and relapse in 117 patients with acute myeloid leukemia: implications for resistance against therapy

Abstract: The instability of the karyotype may play a role in the development of refractoriness of acute myeloid leukemia (AML) to antileukemic therapy. Therefore, in the current study cytogenetic analyses were performed in 117 patients with AML both at diagnosis and at relapse. Changes in karyotype were observed in 38% (36% of initially normal karyotypes, 39% of initially aberrant karyotypes). An evolution of karyotype, ie the acquisition of further aberrations in addition to those present at diagnosis, occurred more f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
57
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 23 publications
9
57
0
1
Order By: Relevance
“…At 3 years, the probabilities of OS and DFS were only 24% (CI: 16-32%) and accordingly 18% (CI: 8-28%), which corresponds to data from the literature. 27,29,39,40 In accordance with many previous studies, we confirmed that the duration of first CR is an important prognostic factor for the achievement of second CR, the duration of OS and DFS from second CR. [21][22][23][24] There was a significant relation between the duration of first CR and the parameters of clinical outcome (rate of second CR, OS and DFS).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…At 3 years, the probabilities of OS and DFS were only 24% (CI: 16-32%) and accordingly 18% (CI: 8-28%), which corresponds to data from the literature. 27,29,39,40 In accordance with many previous studies, we confirmed that the duration of first CR is an important prognostic factor for the achievement of second CR, the duration of OS and DFS from second CR. [21][22][23][24] There was a significant relation between the duration of first CR and the parameters of clinical outcome (rate of second CR, OS and DFS).…”
Section: Discussionsupporting
confidence: 77%
“…Estey et al 41 found that a change in the cytogenetic pattern at first relapse does not influence the prognosis of therapy for first relapse in the great majority of patients. Data observed by Kern et al 29 suggest that cytogenetics at relapse tended to be related to the outcome more strongly than cytogenetics at diagnosis. We have not studied this question among our patient cohort systematically.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…69,70 Discrepancies with other reports may be due to technical reasons or one might speculate that these cases represent treatment-related or even second de-novo AMLs rather than relapses from previous leukaemia. 71 Extensive investigation by FISH and other molecular techniques are warranted to clarify the issue.…”
Section: Npm Dislocation Into Cytoplasm: a Critical Event For Leukaemmentioning
confidence: 99%
“…[23][24][25] Similarly, low resolution SNP array analysis of 27 pairs of diagnosis and relapse adult AML specimens showed that 10 of 11 cases with genomic lesions at diagnosis maintained or added to those lesions at relapse, suggesting proximal clonal relatedness. 26 Likewise, whole genome sequencing of 8 AML diagnosis and relapse pairs compared somatic mutation patterns, indicating the resilience of the dominant diagnosis clone or one of its subclones at relapse.…”
Section: Introductionmentioning
confidence: 99%